Pengaruh Pemberian Biochar Terhadap Perubahan Sifat Kimia Tanah Vertisol dan Pertumbuhan Kacang Hijau (Vigna radiata L.): The Impact of Biochar Application on Alterations in Chemical Properties of Vertisol Soil and the Growth of Mung Bean (Vigna radiata L.) - Alvi Maydayana; Bambang Hari Kusumo; Lalu Arifin Aria Bakti; Rika Andriati Sukma Dewi (LPPM Universitas Mataram, 2023)
Vertisols are soils that have a high cation exchange capacity but tend to have a low organic matter content. Meanwhile, nutrients availability in vertisol tends to be low because these elements are bound by clay particles, so the nutrient availability is limited for plantsThe aim of this research is to investigate the influence of rice husk biochar and corn cob biochar application on the changes in chemical properties of Vertisol soil and the vegetative growth of mung bean (Vigna radiata L.). The study was conducted using a Randomized Complete Block Design (RCBD) with an experimental approach. There were 8 treatments repeated 6 times, resulting in a total of 48 experimental units. The rice husk biochar (P) treatments included the control without rice husk biochar (BSP0), rice husk biochar at a rate of 60 g/kg soil (150 tons/ha) + 2.5 kg soil (BSP1), rice husk biochar at a rate of 30 g/kg soil (75 tons/ha) + 2.5 kg soil (BSP2), and rice husk biochar at a rate of 15 g/kg soil (37.5 tons/ha) + 2.5 kg soil (BSP3). The corn cob biochar (J) treatments included the control without corn cob biochar (BTJ0), corn cob biochar at a rate of 60 g/kg soil (150 tons/ha) + 2.5 kg soil (BTJ1), corn cob biochar at a rate of 30 g/kg soil (75 tons/ha) + 2.5 kg soil (BTJ2), and corn cob biochar at a rate of 15 g/kg soil (37.5 tons/ha) + 2.5 kg soil (BTJ3). The research data were analyzed using Analysis of Variance (ANOVA) at a significance level of 5%. Significant differences between treatments were further analyzed using the Duncan's New Multiple Range Test (BNJ) at a significance level of 5%. The soil analysis was carried out at the Soil Physics and Soil Chemistry Laboratories, Faculty of Agriculture, Universitas Mataram. The results of the research showed that biochar application influenced the chemical properties of the soil (pH, Cation Exchange Capacity, Organic-C) and the growth of mung bean plants in Lombok's Vertisol soil. Biochar did not have a significant effect on the height of mung bean plants at 7 and 14 days after planting (DAP), but it had a significant effect at 21, 28, and 35 DAP. However, the application of biochar did not significantly affect the number of leaves and dry weight of mung bean plants.